O movimento sindical dos trabalhadores e trabalhadoras rurais no nordeste paraense: as motivações dos participantes em Tomé-Açu - MORAES, Lucas Gabriel da Silva (Universidade Federal do Pará, 2022)
The Rural Workers' Union Movement (MSTTR) is one of the main collective actions organized in favor of the fight for better living and working conditions in rural areas. In the Northeast region of Pará State, the fight for rights in this category began in the mid-1950s, with the creation of the first farm workers organizations in the region and, later, with the institutionalization of the fight in 1962. Part of the demands of rural workers were rights that urban workers already had, whether they were: health, social security, labor laws and decent wages, in addition to the main demand, agrarian reform. These and other objectives guided collective actions within the scope of the MSTTR which, in turn, constituted the current structure of representation of rural workers. In Tomé-Açu, the Rural Workers’ Syndicate (STTR) was, for at least 35 years, the only organization that defended the category and represented its interests. This reality has changed since 2006, with the creation of the Tomé-Açu Family Farmers’ Syndicate (SINTRAF) and the Tomé-Açu Rural Employees’ Syndicate (SINDTER), in 2016, changing the dynamics of participation, affiliation and collective actions within the scope of the MSTTR. In relation to these dynamics, the literature of social movements has shown that collective action is not an easy task and may depend on a series of factors to materialize itself, as an example, the motivations. Within this context, the present work aims to identify the motivations for the participation of rural workers in the MSTTR, more specifically, in the Tomé-Açu STTR, in Northeast Pará, trying to analyze its trajectory and the current challenges that are imposed on the collective action. The methodology used started from a qualitative approach using the content analysis technique. During data collection, 34 interviews were carried out with syndicate leaders and rural workers, members and non-members who participate in any of the three rural syndicates in Tomé-Açu. The results of the study showed two bases of motivation, one of them being material, linked to the services and benefits of the syndicate, with rural retirement being the main one; and the other immaterial, being highlighted the syndical representativeness. Among non-members, land was the central motivation, exemplified in the case of the collective action carried out in the Mancha Negra camp. In the process of mobilizing new members, the role of leaders proved to be fundamental, both within the syndicate itself, through the figure of the president, and in the local context, through the action of syndicate delegates. As for the current challenges, signs of a crisis in the STTR were identified, which takes place within the scope of collective actions and reflects the problems that occur in the administration of the syndical organization, with the maintenance of power in the hands of the same group for many years, the prioritization of utilitarianism in the syndicate and the lack of new leaderships who could initiate a renewal of the current management.